Investigation of Pb(II) adsorption by amine group enriched chitosan encapsulated iron oxides doped biochar for soil remediation - Hong-Hue Thi Nguyen; Yong-Ho Choi; Eun-Bi Kim; Yong-Hoon Jeong; Jae-Wook Lee; Kyung-Hee Park; Young-Jun Woo; Sadia Ameen; Dong-Heui Kwak (Carbon Trends, 2025)
We propose the possibility of using chitosan-modified magnetic biochar (CMBC) as a potential green material for treating heavy metals (HMs) that exist and persist in the environment. Different functional groups present on CMBC have been studied by surface analyses such as energy dispersive X-ray (EDX), Fourier transform infrared spectroscopy (FTIR), and X-ray photoelectron spectroscopy (XPS). Herein, Fe serves not only as a contributor to magnetism but also as a facilitator in the formation of bonds with Pb(II). The adsorption efficiency of Pb(II) by CMBC (1 % w/v) reached to ∼97.6 % in 60 min. With 200 ppm at initial Pb(II) concentration, CMBC showed an adsorption capacity of ∼88.75 mg·g−1. The adsorption mechanism of Pb(II) by CMBC was consistent with the pseudo-second-order kinetic model with R2 = 0.9997. During the adsorption of Pb(II) by CMBC, Langmuir isotherms delivered R2 = 0.9993 which was larger than the R2 = 0.9882 of Freundlich isotherm, indicating that Pb(II) adsorption mainly occurred on the surface of CMBC with the interaction between Pb(II) and functional groups. The adsorption efficiency of soluble Pb (Pb in soil) by CMBC reached ∼24.6 % after 5 days and ∼27 % after 7 days. This finding underscores that CMBC is capable of effectively removing HMs, such as Pb, in both aqueous and soil environments.